Венчурні фонди України як інвестиційний інститут - Соломіна, Г. (Схід, 2011)
У статті досліджено динаміку кількості венчурних фондів, вартості їхніх чистих активів,
зміну їх частки в загальній кількості інститутів спільного інвестування. Проаналізовано
динаміку структури активів венчурних фондів, структури портфеля їхніх цінних паперів
за галузями інвестування, розподіл вартості чистих активів за типами інвесторів. Проведено порівняльний аналіз дохідності венчурних фондів та альтернативних об'єктів інвестування. Розроблено пропозиції щодо збільшення інвестиційного потенціалу венчурних
фондів. T he dynamics of amount of venture funds, cost of their clean assets, specific gravity in the general amount of institutes of the joint inv esting and total worth of their clean assets is investigated. The dynamics of structure of
assets of venture funds, structures of brief-case of their securities, is analysed on industries of investing, distribution
of net asset value on the types of investors. The comparative analysis of profitableness of venture funds and alternative objects of investing is conducted. The suggestion in relation to the increase of investment potential of venture funds is worked out .